Cascading effects of calanoid copepod functional groups on the biological carbon pump in the subtropical South Atlantic - Oliveira, Lívia Dias Fernandes de; Bode-Dalby, Maya; Schukat, Anna; Auel, Holger; Hagen, Wilhelm (Frontiers in Marine Science, 2022)
Life strategies, ecophysiological performances and diel vertical migration (DVM) of zooplankton key species affect the efficiency and strength of the biological carbon pump (BCP). However, it is unclear to what extent different functional groups affect the BCP. Depth-stratified day and night samples (0-800 m) from the subtropical South Atlantic were analyzed focusing on the calanoid copepod community. Calanoid abundance, biomass distribution and species-specific impact on the passive (fecal pellets) and active (via DVM) vertical flux of carbon were determined. Species were assigned to different migrant groups where, their contributions were estimated by using the proportion of the migratory community instead of simple day-night differences in biomass. This novel approach leads to more robust flux estimates, particularly for small sample sizes. According to migration ranges and day/night residence depth, functional groups were characterized, i.e. small- and large-scale epipelagic and mesopelagic migrants. Epipelagic small-scale migrants transported respiratory (1.5 mg C m-2 d-1) and fecal pellet (1.1 mg C m-2 d-1) carbon from the upper to the lower epipelagic zone, where the latter can fuel the microbial loop, and thus deep chlorophyll maxima, or be ingested by other zooplankton. Large-scale migrants actively transported up to 10.5 mg C m-2 d-1 of respiratory carbon from the epipelagic layer into the twilight zone. The majority was transported by Pleuromamma borealis (5.7 mg C m-2 d-1) into the upper mesopelagic. In addition, up to 8.0 mg C m-2 d-1 was potentially egested as fecal material by large-scale zone shifters. Mesopelagic migrants transported respiratory (0.2 mg C m-2 d-1) and fecal pellet carbon (0.1 mg C m-2 d-1) even deeper into the ocean. Community consumption of migrants in the epipelagic layer during the night was 98 mg C m-2 d-1, while non-migrants consumed 98-208 mg C m-2 d-1 in the epipelagic zone, with a potential subsequent egestion of 29-62 mg C m-2 d-1. This carbon may fuel omnivorous-detritivorous feeding, the microbial loop and/or may sink as fecal pellets. This case study shows how calanoid functional groups mediate carbon fluxes in the subtropical South Atlantic Ocean and demonstrates how detailed community analyses can elucidate the complexity of pelagic carbon budgets.